RELASI LITURGI DENGAN EKSPRESI BENTUK SAKRAL ARSITEKTUR GEREJA KATOLIK - Purnama Salura; Bachtiar Fauzy; Rudy Trisno (Universitas Katolik Parahyangan, 2015)
This study aims to explore the relationship between the sacred function from the liturgy process and the expression form in the Catholic Church before anda after the 2nd Vatican Council, in Jakarta. which is is the pioneer for the growth and it has the largest number of Catholic Church.The method used in this study were: Firstly, recording the Cases study Church’s building and then re-draw all the cases styudy in detail so that the architectural building and the ornament can be analyzed.Secondly, the relationship between the sacred function concept, liturgy process and form expression concept were used.Thirdly, the analysis between these three items will be triangulated with the user.